Infectious Keratitis: An Update on Role of Epigenetics - Verma, Sudhir; Singh, Aastha; Varshney, Akhil; Chandru, R. Arun; Acharya, Manisha; Rajput, Jyoti; Sangwan, Virender Singh; Tiwari, Amit K.; Bhowmick, Tuhin; Tiwari, Anil (Frontiers in Immunology, 2021)
Epigenetic mechanisms modulate gene expression and function without altering the base sequence of DNA. These reversible, heritable, and environment-influenced mechanisms generate various cell types during development and orchestrate the cellular responses to external stimuli by regulating the expression of genome. Also, the epigenetic modifications influence common pathological and physiological responses including inflammation, ischemia, neoplasia, aging and neurodegeneration etc. In recent past, the field of epigenetics has gained momentum and become an increasingly important area of biomedical research As far as eye is concerned, epigenetic mechanisms may play an important role in many complex diseases such as corneal dystrophy, cataract, glaucoma, diabetic retinopathy, ocular neoplasia, uveitis, and age-related macular degeneration. Focusing on the epigenetic mechanisms in ocular diseases may provide new understanding and insights into the pathogenesis of complex eye diseases and thus can aid in the development of novel treatments for these diseases. In the present review, we summarize the clinical perspective of infectious keratitis, role of epigenetics in infectious keratitis, therapeutic potential of epigenetic modifiers and the future perspective.